Potensi Sanggar Tari Juju Meningkatkan Minat Generasi Z terhadap Seni Tari di Kota Semarang - Imelya Saragih; Muhammad Jazuli (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This research was motivated by the role of dance studios as non-formal art education centers in fostering young people's interest in traditional dance. The object of this research is the Juju Dance Studio located in Semarang City, focusing on the involvement of members who belong to Generation Z. This study aims to determine the potential and role of the Juju Dance Studio in increasing young people's interest in dance and to identify the strategies used in the studio's training and activities. The method used in this study is a qualitative method with a descriptive approach. Data collection was conducted through observation of training activities, interviews with studio managers and members, and documentation of activities related to learning and art performances. The results of the study show that the Juju Dance Studio plays an important role in increasing Generation Z's interest in dance through structured training activities, art performances, and participation in various dance events and competitions. The learning process at the studio is carried out through a tiered class system that includes basic, intermediate, and advanced classes with a variety of dance materials such as Semarangan dance, Nusantara dance, and Pendet dance. In addition, the use of social media as a promotional tool also helps introduce the studio's activities to the younger generation. Involvement in training and performance activities has a positive impact on increasing the confidence of members and fostering young people's appreciation of dance as part of cultural preservation